2021
DOI: 10.1016/j.jcot.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Squat and smile assessment in predicting healing of lower limb fractures fixed with a SIGN nail

Abstract: Background: Irrespective of the treatment method, union is the ultimate goal of any fracture treatment. However, nowadays, rather than the physician-based clinico-radiological methods, the patient-reported outcome measurements assessing their quality of life and function are gaining much popularity. This is specifically true in the part of the world where the patient needs almost complete degree of hip/knee flexion e for social, cultural, religious or occupational reason(s). The ability to squat can assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…24 Functional healing has been assessed using the S&S test, the patient's ability to perform an unassisted active knee range-of-motion squat, which we have shown to indicate earlier healing compared with radiographic evaluation, but its utility as a measure of healing is controversial. 17,20,25,26 Of the 84 patients in our cohort who had an S&S test, 83.3% of them were considered functionally healed which is similar to Scuito et al 17 who found 80.2% of their 89 patient cohort with femoral fractures were able to pass the S&S test at 24 weeks. Our findings comparing S&S with radiographic healing showed a significant correlation between the 2 tests which may add validity to the S&S examination.…”
Section: Discussionsupporting
confidence: 85%
“…24 Functional healing has been assessed using the S&S test, the patient's ability to perform an unassisted active knee range-of-motion squat, which we have shown to indicate earlier healing compared with radiographic evaluation, but its utility as a measure of healing is controversial. 17,20,25,26 Of the 84 patients in our cohort who had an S&S test, 83.3% of them were considered functionally healed which is similar to Scuito et al 17 who found 80.2% of their 89 patient cohort with femoral fractures were able to pass the S&S test at 24 weeks. Our findings comparing S&S with radiographic healing showed a significant correlation between the 2 tests which may add validity to the S&S examination.…”
Section: Discussionsupporting
confidence: 85%
“…Test for painless WB has remained one of the mainstays of determining fracture union in the clinical setting notwithstanding many advances in fracture union assessment 30 . However, in addition to physician-based clinical and radiological methods, evaluations of fracture healing should also incorporate a patient-centered approach which includes patients’ goals and expectations from the healing process as it relates to their physical and mental functioning 21 , 31 . Fascinatingly, we observed that the SIGN nail being a solid locked rod, allows early WB and return to pre-injury daily activities even when the fracture has not radiographically healed.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the S&S test is based on squatting makes it locally relevant—for social, cultural, religious or occupational reasons. Since it can assess the mobility and stability of joints, especially hip and knee, the quality of squatting is said to be a proxy reflection of the functional outcome after fixation of lower limb fracture, particularly in LMICs where other assessment modalities are either expensive or unavailable 31 , 33 .…”
Section: Discussionmentioning
confidence: 99%